Bacteriostatic and Bactericidal Activities of Moxifloxacin against Coxiella burnetii - Rolain, Jean-Marc (American Society for Microbiology, 2001)
The in vitro activity of moxifloxacin against Coxiella burnetii was compared to those of pefloxacin, ofloxacin, and doxycycline. MICs of moxifloxacin ranged from 0.5 to 1 μg/ml for the Nine Mile, Priscilla, and Q212 strains. Moxifloxacin was not bactericidal against C. burnetii at 4 μg/ml.